CORAK HUMANISME DALAM SERIKAT BURUH JAWA TAHUN 1926-1942 - Daya Negri Wijaya (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract:trade union established as a common goal ofworkers in obtaining life insurance and mutual prosperity. But in its development, trade unions met various obstacles both in the internal context where there are workers who do not want to join the union or the external context where the union is under pressure from the investors and the government. However, they are not desperate and trying to fight the goal. Furthermore, they struggle in perkembangannnya teryata not only the interests of the union but also the interests of the people in general such as issues of racial and class and gender gaps. This paper is expected to provide a historical consciousness of the reader in order to use the past as suggestions and lessons learned in designing a better  future.Keywords: national movements, labor, human existence, humanism